The Divine in Modern Hebrew Literature: Conceptions of the Divine - Stahl, Neta (Routledge Jewish studies series, 2020)
Introduction -- Chapter 1: Fin-de-Siécle Jewish Writers on the God of Nature -- Chapter 2: Theomorphism and Modern Hebrew Literature's Search for the Divine: Brenner and Shlonsky as a Case Study -- Chapter 3: Uri Zvi in Front of God -- Chapter 4: Narrative and Providence in the Fiction of S. Y. Agnon -- Chapter 5: "And You Will Hand Me into the Hands of Man": God in the Antiwar Poetry of Yehuda Amichai and Dahlia Ravikovitch -- Epilogue: Pantheism and Its Discontents.